2013
DOI: 10.1590/s0004-27492013000400002
|View full text |Cite
|
Sign up to set email alerts
|

One year results of anti-VEGF treatment in pigment epithelial detachment secondary to macular degeneration

Abstract: Purpose: Pigment epithelial detachment (PED) may be seen in all stages of agerelated macular degeneration (ARMD) and may lead to poor prognosis. In this study, we retrospectively examined the effect of anti-VEGF treatments in ARMD patients with vascularized PED. Methods: Medical records of 15 patients with PED secondary to ARMD were re viewed retrospectively. The diagnosis of PED was made with fundoscopy, fundus fluorescein angiography and optical coherence tomography. Patients were treated with intravitreal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These findings are consistent with prior reports 3–7. Yuksel et al 6 demonstrated that the improved effects of fvPED height changes were most apparent at 1 month and remained stable through 1 year. Bolz et al 8 reported that this therapeutic effect was seen at 1 week suggesting that the beneficial effects of anti-VEGF therapies on fvPED height occur quickly after treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with prior reports 3–7. Yuksel et al 6 demonstrated that the improved effects of fvPED height changes were most apparent at 1 month and remained stable through 1 year. Bolz et al 8 reported that this therapeutic effect was seen at 1 week suggesting that the beneficial effects of anti-VEGF therapies on fvPED height occur quickly after treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Larger clinical trials for the treatment of nAMD have either excluded eyes with PEDs or, if included, have not performed subanalysis of the PED's response to treatment (4–56–7–8–9–10–11–121314–15), so there is limited evidence for the efficacy of anti-vascular endothelial growth factor (VEGF) agents for the treatment of PED from large cohorts. A range of case reports and smaller, mainly retrospective, studies have evaluated the response of PEDs to pegaptanib (a selective anti-VEGF agent), bevacizumab, and ranibizumab (nonselective anti-VEGF agents) in eyes with nAMD (161718192021); however, the outcomes are conflicting and provide no clear guidance for the use of this class of therapy in the treatment of PED.…”
Section: Introductionmentioning
confidence: 99%
“…V ascularized pigment epithelial detachment (PED) is a common variant of neovascular age-related macular degeneration (AMD) and is most often associated with type 1 neovascularization (NV) previously referred to as occult choroidal neovascularization (CNV). [1][2][3][4][5][6][7][8][9][10][11] Pigment epithelial detachments can assume various morphologic configurations, and a number of different terms have been used to describe PED formation in neovascular AMD, including fibrovascular PED, vascularized serous PED (vsPED), and more recently multilayered PED. 3,[12][13][14] Type 1 NV accounts for up to 40% to 50% of newly diagnosed treatment-naïve patients with exuda-tive AMD.…”
mentioning
confidence: 99%